Overall analysis of F CUBED Bd. Solar Water Processors Ltd. - Biswas, Sharon Jennifer Dawson (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2015.